2002
DOI: 10.1139/o01-230
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin and lactoferricin derived from milk: production and applications

Abstract: Bovine lactoferrin is produced on an industrial scale from cheese whey or skim milk. The safety of purified lactoferrin has been confirmed from the results of a reverse mutation test using bacteria, a 13-week oral repeated-dose toxicity study in rats, and clinical studies. In order to apply active lactoferrin to various products, a process for its pasteurization was developed. Subsequently, lactoferrin has been used in a wide variety of products since it was first added to infant formula in 1986. A pepsin hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 24 publications
2
134
0
3
Order By: Relevance
“…Bovine lactoferrin, a byproduct from cheese whey or skim milk, is commercially available as a health food in Japan [114] and has been used in a wide variety of products since it was first added to infant formula in 1986 [115]. Similarly, recombinant human lactoferrin (rhLF), was found in transgenic cow's milk at gram per litre concentrations [116].…”
Section: Future Areas Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine lactoferrin, a byproduct from cheese whey or skim milk, is commercially available as a health food in Japan [114] and has been used in a wide variety of products since it was first added to infant formula in 1986 [115]. Similarly, recombinant human lactoferrin (rhLF), was found in transgenic cow's milk at gram per litre concentrations [116].…”
Section: Future Areas Of Researchmentioning
confidence: 99%
“…Lactoferrins have little toxicity and are very safe, especially when administered orally. The oral toxicity of purified lactoferrin is extremely low and 2000 mg/kg/day did not cause any adverse effects in rats of both sexes [115,117]. Similarly, 434 mg/kg lactoferrin was not toxic for mice [118].…”
Section: Future Areas Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine and human lactoferricin, from N-terminal end of bovine and human lactoferrin, respectively, are known for their ability to improve and modulate the function of host immune system [145][146][147]. Additional, deletion fragments of lactoferrin like the peptide sequence FKCRRWQWRW, corresponding to N-terminal fragment 17-26 of bovine lactoferrin, has demonstrated potent activation of polymorphonuclear leukocytes [21].…”
Section: Table 3 Milk Proteins-derived Peptides With Antiviral and Imentioning
confidence: 99%